Ofatumumab maintenance versus observation in relapsed chronic lymphocytic leukaemia (PROLONG): an open-label, multicentre, randomised phase 3 study. Issue 13 (October 2015) - van Oers, Marinus H J; Kuliczkowski, Kazimierz; Smolej, Lukáš; Petrini, Mario; Offner, Fritz; Grosicki, Sebastian; Levin, Mark-David; Gupta, Ira; Phillips, Jennifer; Williams, Vanessa; Manson, Stephanie; Lisby, Steen; et al.
Summary: Background: Ofatumumab is a human anti-CD20 monoclonal antibody that has proven efficacy as monotherapy in refractory chronic lymphocytic leukaemia. We assessed the efficacy and safety of ofatumumab maintenance treatment versus observation for patients in remission after re-induction treatment for relapsed chronic lymphocytic leukaemia. Methods: This open-label, multicentre, randomised phase 3 study enrolled patients aged 18 years or older from 130 centres in 24 countries who had chronic lymphocytic leukaemia in complete or partial remission after second-line or third-line treatment. Eligible patients had a WHO performance status of 0–2, had a response assessment within the previous 3 months, did not have refractory disease, autoimmune haemolytic anaemia requiring treatment, chronic or active infection requiring treatment, and had not previously received maintenance treatment or autologous or allogeneic stem-cell transplant. Using a randomisation list generated by a central computerised system and an interactive voice recognition system, we randomly assigned (1:1) patients to receive ofatumumab (300 mg followed by 1000 mg 1 week later and every 8 weeks for up to 2 years) or undergo observation. Randomisation was stratified by number and type of previous treatment and remission status after induction treatment (block size of four). Treatment assignment was open label. The primary endpoint was investigator-assessed progression-free survival in the intention-to-treat population. We report the results of a prespecified interim analysis after two-thirds of the planned study events (disease progression or death) had happened. This trial is closed to accrual but follow-up is ongoing. This trial is registered with ClinicalTrials.gov, number NCT00802737 . Findings: Between May 6, 2010, and June 19, 2014, we enrolled 474 patients: 238 patients were randomly assigned to receive ofatumumab maintenance treatment and 236 to undergo observation. One (<1%) patient in the ofatumumab group did not receive the allocated intervention (withdrawal of consent). The median follow-up was 19·1 months (IQR 10·3–28·8). Progression-free survival was improved in patients assigned to the ofatumumab group (29·4 months, 95% CI 26·2–34·2) compared with those assigned to observation (15·2 months, 11·8–18·8; hazard ratio 0·50, 95% CI 0·38–0·66; p<0·0001). The most common grade 3 or higher adverse events up to 60 days after last treatment were neutropenia (56 [24%] of 237 patients in the ofatumumab group vs 23 [10%] of 237 in the observation group) and infections (31 [13%] vs 20 [8%]). 20 (8%) of 237 patients in the ofatumumab group and three (1%) of 237 patients in the observation group had adverse events that led to permanent discontinuation of treatment. Up to 60 days after last treatment, two deaths related to adverse events occurred in the ofatumumab treatment group and five deaths related to adverse events occurred in the observation group; no deaths were attributed to the study drug. Interpretation: These data are important for the development of optimum maintenance strategies in patients with relapsed chronic lymphocytic leukaemia, notably in the present era of targeted drugs, many of which are to be used until progression. Funding: GlaxoSmithKline and Genmab.